2017
DOI: 10.1158/0008-5472.can-16-1839
|View full text |Cite
|
Sign up to set email alerts
|

Differential PI3Kδ Signaling in CD4+ T-cell Subsets Enables Selective Targeting of T Regulatory Cells to Enhance Cancer Immunotherapy

Abstract: To modulate T-cell function for cancer therapy, one challenge is to selectively attenuate regulatory but not conventional CD4 T-cell subsets [regulatory T cell (Treg) and conventional T cell (Tconv)]. In this study, we show how a functional dichotomy in Class IA PI3K isoforms in these two subsets of CD4 T cells can be exploited to target Treg while leaving Tconv intact. Studies employing isoform-specific PI3K inhibitors and a PI3Kδ-deficient mouse strain revealed that PI3Kα and PI3Kβ were functionally redundan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 27 publications
3
92
1
Order By: Relevance
“…We have also reported that PI3Kδ-inactivated mice have a reduced CD8 + T cell response to L. monocytogenes infection (30). On the other hand, it was recently reported that PI3Kδ inhibition selectively affected proliferation and viability in Tregs over conventional CD4 + T cells, thus conferring a therapeutic advantage in combination with a tumor peptide vaccine (31). The relative significance of CD8 + T cells and conventional CD4 + T cells in the antitumor response likely varies by tumor type, but we show here that a reduction in CD8 + T cell function is in some cases sufficient to abrogate the advantages of Treg impairment.…”
Section: Discussionmentioning
confidence: 73%
“…We have also reported that PI3Kδ-inactivated mice have a reduced CD8 + T cell response to L. monocytogenes infection (30). On the other hand, it was recently reported that PI3Kδ inhibition selectively affected proliferation and viability in Tregs over conventional CD4 + T cells, thus conferring a therapeutic advantage in combination with a tumor peptide vaccine (31). The relative significance of CD8 + T cells and conventional CD4 + T cells in the antitumor response likely varies by tumor type, but we show here that a reduction in CD8 + T cell function is in some cases sufficient to abrogate the advantages of Treg impairment.…”
Section: Discussionmentioning
confidence: 73%
“…Likewise, diarrhea and colitis is a frequent side effect of idelalisib in human patients (Coutré et al, 2015). On the other hand, impaired Treg function has a beneficial outcome in the context of tumor immunity, where genetic or chemical inhibition of p110δ promoted tumor regression in several mouse models (Ahmad et al, 2017; Ali et al, 2014). The latter observation has raised interest in testing p110δ inhibitors to enhance immunotherapy response in solid tumors.…”
Section: Pi3k In Innate and Adaptive Immunitymentioning
confidence: 99%
“…Monoallelic expression of an AKT-insensitive FOXO1 mutant in Treg cells resulted in decreased tumor infiltration of activated Tregs accompanied by enhanced activation of tumor-infiltrating cytotoxic T lymphocytes, and in turn increased inhibition of tumor growth in three different preclinical models (Luo et al, 2016). The potential of p110δ inhibitors to enhance antitumor immunity in mice via Treg inhibition was discussed above (Ahmad et al, 2017; Ali et al, 2014). The potential immunostimulatory effects of p110δ inhibitors are being explored in combination with anti-PD-1 antibody in ongoing clinical studies.…”
Section: Therapeutic Targeting Of the Pi3k Pathway In Cancermentioning
confidence: 99%
“…The CTL epitope from HPV16 E7 49-57 (9 amino acid (aa) peptide, RAHYNIVTF, 100 mg/mouse) mixed with synthetic T helper epitope PADRE (13 aa peptide, aK-Cha-VAAWTLKAAa, where "a" is D alanine and Cha is L-cyclohexylalanine, 20 mg/ mouse; both from Celtek Bioscience) and QuilA adjuvant (20 mg/ mouse; Brenntag) were used as the model vaccine in all experiments (16). Three doses of vaccine were administered subcutaneously (s.c.), every seven days (D) in tumor-bearing mice.…”
Section: Vaccinesmentioning
confidence: 99%